Investigating surface proteins and antibody combinations for detecting circulating tumor cells of various sarcomas - Minh-Chau N. Le; Kierstin A. Smith; Pablo J. Dopico; Beate Greer; Morteza Alipanah; Yang Zhang; Dietmar W. Siemann; Joanne P. Lagmay; Z. Hugh Fan (Scientific Reports, 2024)
Abstract Circulating tumor cells (CTCs) have gathered attention as a biomarker for carcinomas. However, CTCs in sarcomas have received little attention. In this work, we investigated cell surface proteins and antibody combinations for immunofluorescence detection of sarcoma CTCs. A microfluidic device that combines filtration and immunoaffinity using gangliosides 2 and cell surface vimentin (CSV) antibodies was employed to capture CTCs. For CTC detection, antibodies against cytokeratins 7 and 8 (CK), pan-cytokeratin (panCK), or a combination of panCK and CSV were used. Thirty-nine blood samples were collected from 21 patients of various sarcoma subtypes. In the independent samples study, samples were subjected to one of three antibody combination choices. Significant difference in CTC enumeration was found between CK and panCK + CSV, and between panCK and panCK + CSV. Upon stratification of CK + samples, those of metastatic disease had a higher CTC number than those of localized disease. In the paired samples study involving cytokeratin-positive sarcoma subtypes, using panCK antibody detected more CTCs than CK. Similarly, for osteosarcoma, using panCK + CSV combination resulted in a higher CTC count than panCK. This study emphasized deliberate selection of cell surface proteins for sarcoma CTC detection and subtype stratification for studying cancers as heterogeneous as sarcomas.